2005
DOI: 10.2169/internalmedicine.44.1247
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dehydroepiandrosterone Sulfate (DHEAS) on Myotonia: Intracellular Studies

Abstract: Objective In order to find some appropriate medicine to suppress myotonia without decreasing muscle strength experiments were performed on myotonic (mto) mice whose Cl channel does not develop due to stop codon and serves as an animal model of myotonia. In myotonic dystrophy dehydroepiandrosterone is low in the serum and it has been reported that intravenous injections of DHEAS to human cases improves myotonia and activities of daily living.Materials and Methods Three pairs of heterozygote mto mice, SWR/J-Clcn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…DM1 may be associated with low circulating dehydroepiandrosterone (DHEA) levels 78 79. An initial pilot study suggested that DHEA may improve myotonia and muscle strength in DM1 80.…”
Section: Managementmentioning
confidence: 99%
“…DM1 may be associated with low circulating dehydroepiandrosterone (DHEA) levels 78 79. An initial pilot study suggested that DHEA may improve myotonia and muscle strength in DM1 80.…”
Section: Managementmentioning
confidence: 99%
“…This is coupled with age-associated increases in insulin resistance, cardiovascular diseases, neurological disorders, and musculoskeletal frailty (42)(43)(44). Moreover, DHEA has biological actions in cell-based systems and animal models that mimic many of the actions of insulin and other hormones important for metabolic, cardiovascular, and neurological function (19,(45)(46)(47)(48)(49). Taken together, these observations have led to the hypothesis that DHEA supplementation may have beneficial health effects in humans to oppose age-related declines in metabolic, cardiovascular, neurological, and musculoskeletal function (50).…”
Section: Discussionmentioning
confidence: 99%
“…It has been implicated in a broad range of biological functions and can be converted to the sex steroid, testosterone. DM1 may be associated with low circulating dehydroepiandrosterone (DHEA) levels (Carter 1985;Nakazora 2005). An initial pilot study suggested that DHEA may improve myotonia and muscle strength in DM1 (Sugino 1998).…”
Section: Dehydroepiandrosterone (Dhea)mentioning
confidence: 99%